PENGARUH PEMBERIAN PUPUK KANDANG AYAM DAN POC TERHADAP PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (Allium cepa L.) - Simanjuntak, Pantas; Sitorus, Efbertias; Panataria, Lince Romauli; Sianturi, Martius Tandem; Saragih, Meylin Kristina (Universitas Methodist Indonesia, 2023)
This study aims to determine the effect of chicken manure and liquid organic fertilizer on shallots (Allium cepa L.). This study used a Randomized Group Design (RAK) with 2 factors. The first factor is chicken manure consisting of 4 levels, namely: K0 = Control (without treatment), K1 = 1.83 kg/plot (equivalent to 15 tons/Ha), K2 = 2.44 kg/plot (equivalent to 20 tons/Ha) and K3 = 3.05 kg/plot (equivalent to 25 tons/Ha). The second factor is POC consisting of 3 levels, namely: P1 = 3 ml/240ml water/plant, P2 = 6 ml/240ml water/plant and P3 = 9 ml/240ml water/plant. Data analysis used analysis of variance and Duncan test. The results showed that chicken manure had a significant effect on plant height, number of leaves, number of tubers per sample, number of tubers per plot, wet tuber weight per sample, wet tuber weight per plot, dry tuber weight per sample and dry tuber weight per plot. Increasing the dose of manure will increase the growth and production of shallot plants. Chicken manure has a significant effect on plant height, number of leaves, dry bulb weight per sample and dry bulb weight per plot, but has no significant effect on the number of bulbs per sample, number of bulbs per plot, wet bulb weight per sample, wet bulb weight per plot. Chicken manure had a significant effect on the dry weight of bulbs per plot, but had no significant effect on plant height, number of leaves, number of bulbs per sample, number of bulbs per plot, wet bulb weight per sample, wet bulb weight per plot and dry bulb weight per sample.